First records of Corydoras polystictus (Siluriformes: Callichthyidae: Corydoradinae) from the province of Misiones, northeast Argentina - Cardoso, Yamila Paula (2015)
Corydoras polystictus has been reported for Argentina only from the records published by Lüling in 1980 and 1982 from the río Gualeguay, an affluent of the lower río Paraná in the province of Entre Ríos. This author stated that the distribution of this species in Argentina would be linked to the middle and lower río Paraná basin. In this note, we provide the first Argentinean records from the río Paraná basin in the province of Misiones.